2020
DOI: 10.1111/eth.13021
|View full text |Cite
|
Sign up to set email alerts
|

Chemical signalling behaviour in intrasexual communication of lizards lacking femoral pores

Abstract: Signals that are used in animal communication may have multiple sensorial channels and functions. Animal communication integrates very distinct mechanisms such as behaviour, morphology and physiological secretions. Chemical signals occur in several contexts and are known to have a role in sexual selection. In many lizards, pheromones secreted through femoral pores are used to attract females and demark territory dominance. In lizard species without femoral pores, however, study of chemical signalling is neglig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Evans (1961) suggested that the limited repertoire of agonistic and courtship behaviours in skinks derives from greater dependence on olfactory stimuli than visual signals for interspecific recognition. In several lizard species, pheromones that mediate agonistic interactions, mate attraction, and territory demarcation are released from femoral pores (Cooper, 1994;Bruinjé et al, 2020). Although we observed some tongueflicking, we observed no femoral or cloacal pores, suggesting that male T. atlantica rely heavily on visual signals during agonistic behaviour, similar to that observed in the skink Carlia jarnoldae (Langkilde et al, 2003).…”
Section: Discussionsupporting
confidence: 76%
“…Evans (1961) suggested that the limited repertoire of agonistic and courtship behaviours in skinks derives from greater dependence on olfactory stimuli than visual signals for interspecific recognition. In several lizard species, pheromones that mediate agonistic interactions, mate attraction, and territory demarcation are released from femoral pores (Cooper, 1994;Bruinjé et al, 2020). Although we observed some tongueflicking, we observed no femoral or cloacal pores, suggesting that male T. atlantica rely heavily on visual signals during agonistic behaviour, similar to that observed in the skink Carlia jarnoldae (Langkilde et al, 2003).…”
Section: Discussionsupporting
confidence: 76%
“…It is important to note that epidermal gland secretions are not the sole source of chemical information in lizards; faeces, cloacal secretions and skin lipids can contain socially relevant chemical stimuli too [ 36 , 39 ]. In other words, species that lack glands are not necessarily constrained by their ability to obtain chemical information [ 78 ]. For example, some lizard species ‘scat pile’, where they essentially have a latrine near their refuges and these act as information centres [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future work could usefully investigate other visual signals and chemical signals to determine whether factors other than body shape may also contribute the decision process of T. septentrionalis. It has been found that Takydromus lizards among species having the visual [51] and chemical [52][53][54][55] communication systems and abilities to signal with conspecifics and alter their behaviour.…”
Section: Discussionmentioning
confidence: 99%